2015
DOI: 10.5433/1679-0359.2015v36n3p1495
|View full text |Cite
|
Sign up to set email alerts
|

Glycerin in cattle feed: intake, digestibility, and ruminal and blood parameters

Abstract: This study aimed to evaluate the effects of glycerin supplements in the diet of beef cattle by assessing intake, apparent nutrient digestibility, ruminal pH, ruminal ammonia concentrations, and blood parameters. The study was conducted at the São Paulo State University (UNESP, Jaboticabal campus) using five crossbred cattle in an experiment employing a 5 x 5 Latin square design. Cattle diet treatments included zero, 50, 100, 150, and 200 g kg -1 dry matter of glycerin. Feed, leftover feed, and faeces were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…Several experiments demonstrated that DMI was not influenced by substituting different energy sources with crude glycerol in the diet (Mach, Bach & Devant 2009, p. 635;Moriel et al 2011, p. 4317;Ramos & Kerley 2012, pp. 896-7;Bartoň et al 2013, p. 55;Leão et al 2013, p. 424;Egea et al 2014, p. 675;Eiras et al 2014, p. 225;van Cleef et al 2014, p. 89;Buttrey et al 2015, p. 3701;Fávaro et al 2015Fávaro et al , p. 1499, which corroborate the findings in the present work. Conversely, a linear reduction in DMI was observed when dry-rolled cornbased diets were replaced by increasing levels of crude glycerol (0 to 15% of the total DM ration) fed to finishing steers (Hales et al 2015, p. 351).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Several experiments demonstrated that DMI was not influenced by substituting different energy sources with crude glycerol in the diet (Mach, Bach & Devant 2009, p. 635;Moriel et al 2011, p. 4317;Ramos & Kerley 2012, pp. 896-7;Bartoň et al 2013, p. 55;Leão et al 2013, p. 424;Egea et al 2014, p. 675;Eiras et al 2014, p. 225;van Cleef et al 2014, p. 89;Buttrey et al 2015, p. 3701;Fávaro et al 2015Fávaro et al , p. 1499, which corroborate the findings in the present work. Conversely, a linear reduction in DMI was observed when dry-rolled cornbased diets were replaced by increasing levels of crude glycerol (0 to 15% of the total DM ration) fed to finishing steers (Hales et al 2015, p. 351).…”
Section: Discussionsupporting
confidence: 87%
“…896-8;Leão et al 2013, pp. 424-6;Eiras et al 2014, p. 225;van Cleef et al 2014, p. 89;Fávaro et al 2015Fávaro et al , p. 1499) and steamflaked corn (Buttrey et al 2015, pp. 3701-2).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The increase occurred probably due to the linear decrease observed in total VFA concentrations (40.1 in G0 and 23.8 mM/L in G30). However, in most of findings reported from studies using high concentrations of crude glycerin (up to 20%), authors did not observe alterations of rumen pH values (Chanjula et al, 2014;Favaro et al, 2015). Low ruminal pH may decrease DMI, fiber digestibility, and microbial yield and thus decrease animal production (Allen, 1997).…”
Section: Discussionmentioning
confidence: 87%
“…Crude glycerin has been recently studied as a great ingredient to prevent metabolic disorders when high inclusions of concentrate were offered to animals in feedlot systems [26,50,73,74]. Because of its own fermentation profile, crude glycerin can avoid severe reduction of ruminal pH and the development of rumen acidosis.…”
Section: Crude Glycerin As a Strategy Ingredientmentioning
confidence: 99%